Development of new OCDM detection techniques for hybrid OCDM/WDM system in optical access network / \c Nasim Ahmed. - Ahmed, Nasim (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2012)
The main goal of this research is to develop a new OCDMA detection technique of hybrid (OCDMA/ WDM) system in optical access networks.